2019
DOI: 10.1590/18069657rbcs20180234
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Mombasa Grass ( Megathyrsus maximus ) Dependence on Nitrogen Fertilization as a Function of Inoculation with Azospirillum brasilense

Abstract: Using biological inputs to improve the efficiency of nitrogen fertilizers represents an alternative for the cultivation of grasses in tropical regions. Azospirillum brasilense is a species of plant growth promoting bacteria widely studied and used in inoculants. Thus, this study aimed to evaluate the performance of Mombasa grass (Megathyrsus maximus) in association with A. brasilense and nitrogen (N) fertilization.The study was conducted under field conditions in Araguaína-Tocantins State, between December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
11

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 41 publications
0
15
0
11
Order By: Relevance
“…in different sites of Brazil and the combination with N-fertilizer (40 kg ha of N) increased biomass production by 15% and of protein by 25% in comparison to the control receiving only N-fertilizer (Hungria et al 2016). Other studies confirmed the good performance of these strains of A. brasilense with brachiarias (Bulegon et al 2016; Guimarães et al 2016; Leite et al 2018a, b), and also with another important pasture in Brazil, panicum Panicum maximum , = Megathyrsus maximus ) (Leite et al 2019). In addition to A. brasilense , positive results were reported for brachiaria inoculated with Bacillus sp.…”
Section: Main Inoculated Cropsmentioning
confidence: 63%
“…in different sites of Brazil and the combination with N-fertilizer (40 kg ha of N) increased biomass production by 15% and of protein by 25% in comparison to the control receiving only N-fertilizer (Hungria et al 2016). Other studies confirmed the good performance of these strains of A. brasilense with brachiarias (Bulegon et al 2016; Guimarães et al 2016; Leite et al 2018a, b), and also with another important pasture in Brazil, panicum Panicum maximum , = Megathyrsus maximus ) (Leite et al 2019). In addition to A. brasilense , positive results were reported for brachiaria inoculated with Bacillus sp.…”
Section: Main Inoculated Cropsmentioning
confidence: 63%
“…B.K.Simon & Jacobs (syn. Panicum maximum) genotypes Zuri Guinea (Sá et al 2019b) and Mombassa (Leite et al 2019a). However, the great majority of the pastures in Brazil and worldwide is already established, and nothing is known on the feasibility of inoculation of PGPB to boost plant growth and forage biomass production under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by [9] in M. maximus cv. BRS Zuri, in this same dose of N, and by [41], in M. maximus cv. Mombasa, with A. brasilense Ab-V5 + Ab-V6, regardless of the associated N dose.…”
Section: Nutritional Value Of Mavuno Grass Crude Protein (Cp) In the mentioning
confidence: 94%